STUDENT’S PERCEPTION OF SCIEnNCE LEARNING CARRIED ONLINE OR OFFLINE - Nabilah, Afifah; Rahayu, Annisa Fitria (SEMESTA: Journal of Science Education and Teaching, 2024)
This research aims to see the perceptions of SMP N 1 Sawahlunto students regarding science learning which is carried out directly and indirectly. The type of research used in this research was quantitative descriptive method. And sampling technique used in this research was the proportionate stratified random sampling. The sample in this study consisted of 60 students at SMP N 1 Sawahlunto, such as 30 student of 7th grade and 30 student of 8th grade. The data collection techniques using an instrument in the form of a questionnaire. The research result shows that online and offline science learning has its own advantages and disadvantages. Even though it is one solution when offline learning cannot be implemented, online learning has many inhibiting factors, like communication tools, internet access, and learning media. This research concluded that students of SMP N 1 Sawahlunto prefer learning carried out offline compared to online.